Human Trafficking in Akachi Adimora-Ezeigbo Trafficked (2008) - Ibanga, Grace Itoro (NIU Journal of Humanities; Vol 4 No 4 (2019): KIU Journal of Humanities, Vol. 4 No. 4, December 2019, 2020)
The evil of human trafficking has often been propagated only on the social media for many years, and people have had to doubt the reality of these reports. Akachi Adimora-Ezeigbo has not only creatively visualised the evil of human trafficking, but has also made the reader to feel the forceful involvement of the innocent youth in the exercise of human trafficking. The creative depth of Trafficked is characterised by the stark reality of social and moral issues in Nigerian communities, often caused by the Nigerian immigrants in Asia, Europe and America. The novel exposes the degeneration perpetrated by unscrupulous adults and their inordinate quest to amass wealth. This paper portrays Adimora-Ezeigbo’s advocacy for the re-evaluation of the social, moral and cultural values which underscore the rehabilitation of the Nigerian youth to ensure better living conditions and the achievement of human labour and dignity.